Case Report: Case of cardiac metastases from melanoma, treated by stereotactic radiotherapy, using a MICRA implant - Belbachir, Mehdi; Danthez, Nicolas; Rotzinger, David; Panagiotis, Antiochos; Pruvot, Etienne; Vallet, Veronique; Gondre, Maude; Berthod, Gregoire; Latifyan, Sofia; Demicheli, Rita; Schiappacasse, Luis (Frontiers in Cardiovascular Medicine, 2025)
Metastatic melanomas with prolonged survival are becoming increasingly common. We present the case of a 47-year-old man with melanoma who developed asymptomatic cardiac metastases, whose prognosis depended on their response to either systemic or focal treatment. Consequently, a CyberKnife radiotherapy treatment was performed using a pacemaker for tracking. Instead of using a pacemaker lead, we report here the successful use of a leadless pacemaker (Micra, Medtronic) as a fiducial reference for the tracking, which proved to be reproducible during all sessions. The planning target treatment volume was 161.58 cm3. The radiotherapy treatment was well tolerated, and follow-up cardiac CT scans performed at 1 month and 4 months after the treatment showed an approximately 30% reduction in the lesions size. The size reduction was attributed to the focal radiotherapy treatment, as the other metastatic lesions were progressively worsening during the same period. This case report highlights the feasibility of using a leadless pacemaker as a tracking fiducial for the CyberKnife treatment of high-volume cardiac metastatic lesions.